Workshop videos for requirements communication. Issue 4 (November 2016) - Fricker, Samuel; Schneider, Kurt; Fotrousi, Farnaz; Thuemmler, Christoph
Abstract Shared understanding of requirements between stakeholders and the development team is a critical success factor for requirements engineering. Workshops are an effective means for achieving such shared understanding. Stakeholders and team representatives can meet and discuss what a planned software system should be and how it should support achieving stakeholder goals. However, some important intended recipients of the requirements are often not present in such workshops: the developers. Thus, they cannot benefit from the in-depth understanding of the requirements and of the rationales for these requirements that develops during the workshops. The simple handover of a requirements specification hardly compensates the rich requirements understanding that is needed for the development of an acceptable system. To compensate the lack of presence in a requirements workshop, we propose to record that requirements workshop on video. If workshop participants agree to be recorded, a video is relatively simple to create and can capture much more aspects about requirements and rationales than a specification document. This paper presents the workshop video technique and a phenomenological evaluation of its use for requirements communication from the perspective of software developers. The results show how the technique was appreciated by observers of the video, present positive and negative feedbacks from the observers, and lead to recommendations for implementing the technique in practice.